Influence of Roughness Factor on the Bearing Characteristics of Rock-Socketed Piles - Zhilin Wang; Qingye Shi; Hongming Li; Tao Xiao; Zhihao Tang; Xiang Huang; Bai Yang (Buildings)
With the rapid development of the national economy, the construction of super high-rise buildings, long-span bridges, high-speed railways, and transmission towers has become increasingly common. It is also more frequent to build structures on karst foundations, which imposes higher demands on foundation engineering, especially pile foundations. To study the influence of the roughness factor (RF) on the bearing characteristics of rock-socketed pile, model pile load tests were conducted with different RF values (0.0, 0.1, 0.2, and 0.3) to reveal the failure modes of the test pile, analyze the characteristics of the load–displacement curves and the axial force and resistance exertion law of the pile, and discuss the influence of the RF on the ultimate bearing capacity of the test pile. Based on the load transfer law of test piles, a load transfer model considering the relative pile–soil displacement and the shear dilatancy effect of pile–rock is established to analyze its load transfer characteristics. The results show that the failure mode of the test pile is splitting failure. The load–displacement curves are upward concave and slowly varying. The pile side resistance and the pile tip resistance mainly bear the load on the pile top. As the load on the pile top increases, the pile tip resistance gradually comes into play, and when the ultimate load is reached, the pile tip resistance bears 72.12% to 79.22% of the upper load. The pile side resistance is mainly borne by the rock-socketed section, and the pile side resistance increases sharply after entering the rock layer, but it decreases slightly with increasing depth, and the peak point is located in the range of 1.25D below the soil–rock interface. Increasing the roughness of the pile can greatly improve the ultimate bearing capacity. In this study, the ultimate bearing capacity of the test pile shows a trend of increasing and then decreasing with the gradual increase in RF from 0.0 to 0.3, and the optimal RF is 0.2. The load transfer model of pile–soil relative displacement and pile–rock shear dilatancy effect, as well as the pile tip load calculation model, were established. The calculation results were compared with the test results and engineering measured data, respectively, and they are in good agreement.